(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
This paper examines the impact of transport infrastructure, as an important determinant of transport costs, on trade between Bosnia and Herzegovina and Bosnia and Herzegovina’s fifteen largest trading partners. The estimation is based on a gravity model and panel data for the years 2005 to 2014. Transport costs have been estimated on the basis of distance, geography and quality of transport infrastructure, as well as on sets of "dummy" variables, such as the impact of borders, language or "dummy" variables for identifying whether a country is surrounded by land or sea. The results can be summarized as follows: (i) the quality of infrastructure and logistics is an important determinant of trade performance; (ii) the importance of distance is not diminished when the quality of infrastructure is included; (iii) Bosnia and Herzegovina trades with countries with which it shares a common language – ceteris paribus – twice as much as with others. Keywords: Bosnia and Herzegovina, trade, transport infrastructure, gravity model